Antitermination by both the promoter and the leader regions of an Escherichia coli ribosomal RNA operon. - Holben, W E (1985)
RNA polymerase initiating at Escherichia coli ribosomal RNA promoter-leader regions can efficiently read through factor rho-dependent termination signals. Dissection of the promoter-leader region reveals that the ability to read through termination signals is conferred independently by both promoter and leader regions. Events in the leader also affect the transcription rate of structural genes downstream of the leader. When cells are grown in rich medium, the rrnC leader reduces transcription by a factor of approximately 4 when downstream of the rrnC promoters and by a factor of 2 when downstream of the lac promoter.